Universal Health Coverage Knowledge and Experiences Among Primary Health Care Workers in Jordan: A Qualitative Study - RM, Hala Bawadi, RN; RN, Zaid Al-Hamdan; RN, Rowaida Al-Maaitah; Jaradat, Diana Ali; RN, Ahmad H. Al-Nawafleh; MD, Mohammad Al-Hamdan; MD, Awab Al Hamdan (Journal of Posthumanism, 2025)
The purpose of this qualitative study was to assess Jordanian nurses’ knowledge and experiences with universal health coverage (UHC), including identifying challenges and facilitators in applying it in primary health care settings. Eight nurses were interviewed to explore their knowledge of UHC in general. In the paper described here, qualitative analysis methodology was used to answer the proposed research questions. Analysis of the data revealed the following findings: a lack of information about UHC, barriers/challenges to applying/implementing UHC in PHC, facilitators to apply/implement UHC in PHC, and suggested solutions to apply/implement UHC in primary health care settings. Implications for nursing practice, education, and future research are noted. In conclusion, this study suggests that, because participants suggest that UHC application is an important health care choice, nurses and health care professionals need to consider it in their practice and education.